2018
DOI: 10.3390/ma11050736
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Imaging for Inspecting Transparent Aesthetic Defects in a Polymeric Polarizer with Black and White Stripes

Abstract: Machine vision systems have been widely used in industrial production lines because of their automation and contactless inspection mode. In polymeric polarizers, extremely slight transparent aesthetic defects are difficult to detect and characterize through conventional illumination. To inspect such defects rapidly and accurately, a saturated imaging technique was proposed, which innovatively uses the characteristics of saturated light in imaging by adjusting the light intensity, exposure time, and camera gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Authors in [223]- [229] considered inspecting polarising film defects, according to the fact that polarising film is a key component in LCDs. Special aesthetic defects in polymeric film polarizers have nearly identical reflectivity and transmissivity as normal regions.…”
Section: Othermentioning
confidence: 99%
See 3 more Smart Citations
“…Authors in [223]- [229] considered inspecting polarising film defects, according to the fact that polarising film is a key component in LCDs. Special aesthetic defects in polymeric film polarizers have nearly identical reflectivity and transmissivity as normal regions.…”
Section: Othermentioning
confidence: 99%
“…Such defects, in the industry known as "convex or concave points", have extremely low contrast and are difficult to image under normal illumination. Authors in [224]- [227], [229] defined them as "transparent defects", such as dents, bulges and transparent impurities. Because of their extremely low contrast, these transparent points are the main obstacle to detecting defects in polymeric polarizers with existing detection technology.…”
Section: Othermentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies [7,[13][14][15], we have focused on an imaging mechanism for transparent microdefects, such as dents and bumps, and proposed a so-called saturated imaging method to obtain high-contrast defect images. Through simulation and experimentation, we have found that the saturated image of a defect varies regularly with its stereo shape.…”
Section: Introductionmentioning
confidence: 99%